A study on dinescape and customers' behavioral intention at hipster cafes in Penang / Suria Sulaiman - Sulaiman, Suria; Zamzuri, Nurul Ain; Abd Hakim, Fairuz; Hashim, Norliana (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
According to scholars, there is lack of research focus on dinescape and customers’ behavioural intention at hipster cafes. Moreover, hipster cafes are under fierce competition to attract and maintain customers as the worldwide market evolves rapidly. To succeed in their core business, restaurateurs must be concerned about the elements that impact client happiness, which leads to a desire to return. Therefore, the present study investigate the effects of dinescape on customers’ behavioral intention at hipster cafes in Penang. The data from 150 respondents has been analysed by using Statistical Package for Social Sciences (SPSS) software. The findings revealed that all DINESCAPE dimensions suggested have positive relationship on customers’ behavioural intention at Hipster café in Penang. In conclusion, DINESCAPE has a wide range of potential applications in assisting researchers and restaurateurs in better understanding of customers perceive on physical surroundings.